Literary portrait of Kadyrbek Natho - Karina S. Tkhakakhova; Lidiya M. Dovletkireeva (Кавказология, 2024)
The article is a general overview of the creative heritage of the talented Circassian-American writer of the XX-XXI centuries Kadyrbek Natkho (1927-2021). The problem of poor knowledge of his multi-genre and multilingual prose is noted. The authors give a brief description of such works as “In Search of Oneself”, “The Legend of the Great Abduction”, “Alienated”, “Circassian History”, as well as a series of author’s fairy tales about the Caucasian world. Within the framework of intercultural communication, three main “geographical” vectors have been identified in the literary heritage of Natkho. The first one focuses on the North Caucasus, the second – on the realities of the United States of America, the third – on the patterns of Western European culture. Authors of the article pay great attention to the poetical aspects related to the theme, philosophical idea, artistic conflict, character system and expressive means of the analyzed texts. The conclusion is made about the need for a more thorough and detailed study of K. Natkho’s deeply humanistic and peacemaking works in the future, their popularization in secondary schools, higher educational institutions and the media.